2015
DOI: 10.1186/s13045-015-0152-2
|View full text |Cite
|
Sign up to set email alerts
|

Angptl4 is upregulated under inflammatory conditions in the bone marrow of mice, expands myeloid progenitors, and accelerates reconstitution of platelets after myelosuppressive therapy

Abstract: BackgroundUpon inflammation, myeloid cell generation in the bone marrow (BM) is broadly enhanced by the action of induced cytokines which are produced locally and at multiple sites throughout the body.MethodsUsing microarray studies, we found that Angptl4 is upregulated in the BM during systemic inflammation.ResultsRecombinant murine Angptl4 (rmAngptl4) stimulated the proliferation of myeloid colony-forming units (CFUs) in vitro. Upon repeated in vivo injections, rmAngptl4 increased BM progenitor cell frequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 74 publications
0
20
0
Order By: Relevance
“…Strikingly, and in contrast to what has been proposed (Maryanovich et al, 2018), aged CARc did not exhibit changes in expression of crucial prohematopoietic factors such as Cxcl12, Scf or Angpt1. Nonetheless, we did note significant downregulation of Wnt-inhibitory factor (Wif1), Angptl4 and Npy, associated to the modulation of HSC function ( Figure 4I and 5E) (Park et al, 2015;Schumacher et al, 2015;Singh et al, 2017). Moreover, aging was linked to a repression of gene categories associated to ECM organization, collagen formation and adhesive interactions, which was strongest in mesenchymal cells but also evident in ECs.…”
Section: Increased Proinflammatory Signatures In Aged Bm Stromamentioning
confidence: 87%
“…Strikingly, and in contrast to what has been proposed (Maryanovich et al, 2018), aged CARc did not exhibit changes in expression of crucial prohematopoietic factors such as Cxcl12, Scf or Angpt1. Nonetheless, we did note significant downregulation of Wnt-inhibitory factor (Wif1), Angptl4 and Npy, associated to the modulation of HSC function ( Figure 4I and 5E) (Park et al, 2015;Schumacher et al, 2015;Singh et al, 2017). Moreover, aging was linked to a repression of gene categories associated to ECM organization, collagen formation and adhesive interactions, which was strongest in mesenchymal cells but also evident in ECs.…”
Section: Increased Proinflammatory Signatures In Aged Bm Stromamentioning
confidence: 87%
“…(22) We recently reported that A1AT purified from human plasma binds polyunsaturated fatty acids (FAs) like α-linoleic and oleic acid, and that only FA-bound forms of A1AT increase the expression and release of ANGPTL4 in human bloodadherent monocytic cells and in primary human lung microvascular endothelial cells. (23,24) The above functional differences between FA-free and FA-bound forms of A1AT led us to hypothesize that these 2 forms may express distinct immunomodulatory activities during neutrophil activation. Neutrophils account for about 50-75 % of circulating leukocytes, and during inflammation they are the first immune defense cells to arrive and function via multiple intra-and extracellular mechanisms.…”
Section: Caspase-1 Inhibition Assaymentioning
confidence: 99%
“…3 Moreover, it is essential to maintain the functional capabilities of the BM during storage prior to transplantation. [4][5][6][7][8] The characterization of many cytokines involved in the control of hematopoiesis led to intense investigation into their potential use "in vitro" to expand progenitor cell numbers. [9][10][11][12] The collected data suggests that this may be an effective therapeutic strategy to reduce relapse after transplantation; however, selection and expression of cytokines must be carefully considered to minimize adverse effects on hematopoiesis.…”
Section: Introductionmentioning
confidence: 99%